ANALISIS QOS (QUALITY OF SERVICE) PADA JARINGAN INTERNET (STUDI KASUS: FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA) - Yanto, Yanto (Jurusan Informatika Universitas Tanjungpura, 2013)
Faculty of Engineering University ofTanjungpura as one of the government educationalinstitutions take an active role in the intellectual lifeof the nation, requiring infrastructure and take advantage of advances in information technology toachieve optimal results, such as the internet. Thedevelopment of the Internet and network lately hasmade IP (Internet Protocol), which is the backboneof networking-based TCP / IP is rapidly becomingobsolete. QoS (Quality of Service) is technology thatapplied to the WAN (Wide Area Network) thatallows network administrators to be able to handlea variety of effects due to congestion (congestion) onthe traffic flow of packets in the network. QoSparameters are delay / latency, jitter, packet loss,throughput, MOS, echo cancellation and PDD. QoSparameters that measured are delay, jitter,throughtput, packet loss and MOS (Mean OpinionScore). Result of measurement of QoS parametersthat have been made, value delay was 3.39 withgood index, jitter was 1.50 with bad index,throughput was 1 with bad index, packet loss was 4with very good index and MOS was 2.34 with lessthan good index, so the average total of QoSparameters was 2.45 with index Enough and withit’s percentage was 61.25% in the TIPHONstandard, thus it can be concluded that the internetof Faculty of Engineering University ofTanjungpura belonging to unsatisfactory standardbased on the standard of TIPHON (Joesman 2008)with a rating of < 95%.